The Effect of Instagram Promotion and Whatsapp Online Consultation on the Decision to do Outpatient Treatment at Dr. Yati Zarnudji Main Inpatient Clinic - Siti Marini; Sumardjono Sumardjono; Dimas Ari Darmantyo; Yustiana Wardhani (Universitas Binaniaga Indonesia, 2022)
This research purposes to determine the effect of promotion through Instagram social media and WhatsApp online consultation services in influencing the patient's decision to do outpatient treatment at Dr. Yati Zarnudji Main Inpatient Clinic . This research uses a quantitative method. The sample in this research was 145 outpatient Dr. Yati Zarnudji Main Inpatient Clinic determined by purposive sampling method. The research instrument used a closed questionnaire and analyzed using multiple regression analysis. The results of this research indicate that the promotion of Instagram and WhatsApp online consultation services partially and simultaneously have an influence on the decision to do outpatient (service purchase decisions). This research has contributed to the management of Dr. Yati Zarnudji Main Inpatient Clinic related to promotional strategies and policies through Instagram and the ongoing online whatsapp consultation service.